Designing An Athlete Selection Application Using The Topsis Method - Napitupulu, Erikson Josua; Arkhiansyah, Yuni; Karnila, Sri (Prosiding International conference on Information Technology and Business (ICITB), 2023)
Athletes are a profession that is of great interest to young people in various sports. Psychological factors that support success and the role of coaches in sports are very necessary for the success of talented athletes in their fields. Currently, coaches have certain training programs that aim to increase the athlete's agility, strength, and speed. This program is felt to be less effective because decision-making is done by considering the weighting of two categories, namely physical and psychological. The weight of the criteria obtained will assist coaches in maximizing the physical and psychological abilities of athletes in order to achieve the expected championship targets. For this reason, a plan was created to select talented athletes using the Topsis method (Technique for Others Reference by Similarity to Ideal Solution). This design is facilitated by an Android-based interface with simple logic, an easy-to-understand category calculation input process, and a mathematical model for determining the best athletes so that it can help coaches and be effective in selecting talented athletesKeywords: athletes, training programs, system design, criteria weights, TOPSIS